Human Resource Management to Improve Organizational Commitment and Performance - Rukmana, Dany; Nanda, Nur Alfiah; Nurjanah, Esa; Amelia, Tiara; Faiz , Hilmi Achmad; Husein; Sekarini, Ratih Ayu (International Journal of Integrative Sciences, 2025)
This study aims to test and analyse the influence of human resource management variables, and commitment to organisational performance. This research is a quantitative study to test the research hypothesis. The study took SMK Muhammadiyah 6 Jakarta teachers as the research site, with the determination of the sample using saturated sampling technique so that 50 respondents were used. Data were collected through distributing questionnaires and data were analysed using multiple linear regression. The results of the analysis found that: 1) there is a positive and significant influence between human resource management variables on organisational performance, with the amount of influence 52.4%, 2) there is a positive and significant influence between commitment variables on organisational performance, with the amount of influence 57.1%, 3) there is a positive and significant influence between human resource management variables, commitment, and organisational performance, with the amount of influence 63.9%